Legal Implications and Sanction Enforcement for Violations of Employment Social Security Law - Pahlawan, Sandra Dwi Putri; Rasji, Rasji (Jurnal Ilmu Hukum Kyadiren, 2026)
The right to Employment Social Security constitutes a concrete manifestation of human rights as guaranteed under Article 28H(3) of the 1945 Constitution. The state fulfills this mandate through the National Social Security System administered by the Social Security Agency (BPJS), with Article 15(1) of the BPJS Law requiring companies to register both themselves and their workers. However, numerous violations—ranging from the deprivation of workers’ rights in Solo related to BSU and JHT benefits to cases of maladministration and contribution embezzlement at PT WIN and CNN Indonesia—reveal a significant gap between normative provisions and actual implementation. This study examines the legal consequences faced by companies that fail to comply with Jamsostek membership obligations and evaluates the effectiveness of sanctions under Law No. 24 of 2011. Using a normative-juridical method, the study identifies three principal legal consequences: progressive administrative sanctions, the obligation to provide full benefits to affected workers, and criminal sanctions, including dual liability for corporations and their managers. Although the legal framework is comprehensive, its effectiveness remains low due to weak supervisory mechanisms and slow criminal enforcement.